Synovial Cysts in the Temporomandibular Joint: a Case Report and Critical Review of the Literature - Ynn Maribo; Kasper Stokbro; Esben Aagaard; Stine Rosenkilde Larsen; Torben Thygesen (Stilus Optimus, 2019)
Background: Synovial cysts of the temporomandibular joint are rare and treatment is based on consensus from cases reporting unilateral successful outcomes. A patient with a synovial cyst is presented, treated with successful surgical excision of the cyst, but without remission of joint symptoms. Furthermore, the case is supplemented by a critical, literature review. Methods: This case report deals with a patient with a synovial cyst that presented with temporomandibular joint (TMJ) pain and reduced mouth opening. Magnetic resonance imaging verified a TMJ cyst. Results: Surgical excision removed the synovial cyst, and the patient was followed-up for 4 years, with no recurrence of the cyst. Despite successful excision of the cyst, the symptoms did not subside, and the patient is still in treatment. The critical, literature review found 23 case reports describing 24 synovial cysts. In addition, 4 cases were included as their synovial cysts were erroneously described as ganglion cysts. In 4 cases, histological diagnosis could not be confirmed, and they were excluded. All cases described treatment by surgical excision without recurrence. The reported median follow-up was 10 months and postoperative TMJ symptoms were rarely examined or described. Conclusions: The temporomandibular joint symptoms may persist despite successful removal of the synovial cyst. Furthermore, the 4 identified synovial cysts, mislabelled as ganglion cysts, represents almost a quarter of the cases of the reported synovial cysts. Correct labelling and reporting of synovial cysts are still imperative to describe the diverse aspects of treatment outcomes following surgical excision.